Getting through the crisis together: do friendships contribute to university students’ resilience during the COVID-19 pandemic? - Kulcar, Vanessa; Bork-Hüffer, Tabea; Schneider, Ann-Malin (Frontiers in psychology, 2022)
Social contacts and social support represent resources that contribute to resilience. However, the COVID-19 pandemic and the associated measures, including contact restrictions, posed challenges for young adults’ social networks, in particular for their friendships. Employing a mixed-method approach, we investigated the pandemic’s effects on friendships and their role in successfully navigating the crisis. We combined a qualitative approach based on narratives and in-depth interviews and a quantitative approach based on online surveys focusing on university students in Austria. Longitudinal data collections allowed investigating changes and developments as the pandemic progressed. Results indicate profound challenges for participants’ friendships and difficulties in both building new and maintaining existing friendships. This also impaired the provision of social support by friends, scattering participants’ social resources and diminishing their resilience rather than strengthening it. Altogether, the results of this longitudinal study suggest a lasting negative effect of the pandemic on friendships for students.
Gesehen am 11.04.2025